The legacy of Pierre Bourdieu : critical essays - Susen, Simon; Turner, Bryan S. (London : Anthem Press, 2011)
This volume explores the sociological legacy of the late Pierre Bourdieu through an examination of the intellectual division between his reception in the world of French social sciences and his reception in the Anglophone world.
1. Between Structuralism and Theory of Practice: The Cultural Sociology of Pierre Bourdieu / Alex Skinner -- 2. Pierre Bourdieu: Unorthodox Marxist? / Bridget Fowler -- 3. From Marx to Bourdieu: The Limits of the Structuralism of Practice / Bruno Karsenli -- 4. Durkheim and Bourdieu: The Common Plinth and its Cracks / Tank Wareh -- 5. With Weber Against Weber: In Conversation With Pierre Bourdieu / Simon Susen -- 6. Bourdieu and Nietzsche: Taste as a Struggle / Keijo Rahkonen -- 7. Elias and Bourdieu / Mustafa Emirbayer -- 8. Bourdieu and Adorno on the Transformation of Culture in Modern Society: Towards a Critical Theory of Cultural Production / Simon Susen -- 9. The Grammar of an Ambivalence: On the Legacy of Pierre Bourdieu in the Critical Theory of Axel Honneth / Mauro Basaure -- 10. Pierre Bourdieu and the Sociology of Religion / Bryan S. Turner -- 11. Bourdieu's Sociological Fiction: A Phenomenological Reading of Habitus / Bruno Frere -- 12. Overcoming Semiotic Structuralism: Language and Habitus in Bourdieu / Hans-Herbert Kogler -- 13. Social Theory and Politics: Aron, Bourdieu and Passeron, and the Events of May 1968 / Derek Robbins -- 14. Intellectual Critique and the Public Sphere: Between the Corporatism of the Universal and the Realpolitik of Reason / Steven Corcoran -- 15. Practice as Temporalisation: Bourdieu and Economic Crisis / Lisa Adkins.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Bourdieu, Pierre, -- 1930-2002.; Sociology -- Philosophy; Social sciences -- Philosophy